Reconstruction of The Digital Number-Based Straight Kick Strength Detection Tool in Pencak Silat - Putri, Selvani Apriliana; Agusni, Dhani; -, Sriningsih (Universitas Suryakancana, 2025)
This study aims to find out how the process of reconstruction of the digital number-based straight kick power detection tool in pencak silat. This type of research uses the ADDIE (analysis, design, development, implementation, evaluation) development method. The analysis stage identifies the needs and characteristics of users, Design makes 3D prototype designs, Development makes and tests products, Implementation of product trials to SME athletes, This evaluation is carried out on each product development. The data analysis technique uses a presentation test whose purpose is to present data that has been obtained from experts and athletes. The subjects of this study are 3 experts and 10 athletes of STKIP PASUNDAN pencak silat UKM, the instrument used for the validation of the tool is in the form of questionnaires or questionnaires. The results of this study were obtained that the straight kick strength detection tool was declared feasible with a penalty score of 78% and the tool could detect the straight kick force with 80% success. So it can be concluded that this digital number-based straight kick strength detection tool is suitable for use in the training process and can detect the force of straight kicks. Therefore, this tool can be recommended as a safe, effective training tool and a reference for coaches and athletes to evaluate the strength of the kick objectively.